Research on distributed cooperative algorithm based on signal-to-noise ratio coefficient with double thresholds - Li Zhanxiong; Liu Liping; Fang Liang; Lv Jiafeng; Wang Ci (Dianzi Jishu Yingyong, 2024)
In order to solve the problem that the traditional energy detection algorithm has poor detection performance due to the fixed decision threshold when the signal-to-noise ratio is low, this paper studies a dual-threshold cooperative energy detection algorithm that can change with the signal-to-noise ratio coefficient. The threshold value of the algorithm is adaptively adjusted according to the signal-to-noise ratio coefficient. At the same time, considering that the centralized cooperation is incompetent due to the problem of over-reliance on the fusion center, the distributed cooperation method is used to integrate the information detected by each cognitive user. The energy value is compared with a dynamic threshold. Finally, it is proved that the algorithm has better detection performance comparing with the two traditional algorithms.